2008
DOI: 10.1287/ited.1080.0015
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Business Modeling Using Spreadsheets

Abstract: B efore spreadsheets, modeling of business concerns required some competency in mathematics (algebra, calculus, statistics, and probability) and in computer programming, skills that are rather intimidating for the average business executive and management school student. However, the spreadsheet and the personal computer revolution challenged that paradigm. With its simple intuitive interface, direct interactivity, and universal presence, the humble spreadsheet has made business modeling much easier and has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
(18 reference statements)
1
12
0
1
Order By: Relevance
“…Focusing in the field of business administration, spreadsheets and consequently the spreadsheet use competence is very important as stated by (Walters & Pergola, 2012). Spreadsheets' importance is highlighted in a considerable volume of literature, in general, and its use in business administration, in particular (Ahmed, 2008;Leong & Cheong, 2008;Mays, 2015). All these works, and other conceptually and thematically similar ones, share a common element.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Focusing in the field of business administration, spreadsheets and consequently the spreadsheet use competence is very important as stated by (Walters & Pergola, 2012). Spreadsheets' importance is highlighted in a considerable volume of literature, in general, and its use in business administration, in particular (Ahmed, 2008;Leong & Cheong, 2008;Mays, 2015). All these works, and other conceptually and thematically similar ones, share a common element.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Leong and Cheong (2008) found that students relatively stronger in Excel skills are generally weaker in modelling and vice versa.…”
Section: Students Argue That: " Overall I Think the Teaching Methodsmentioning
confidence: 96%
“…• Module 7-selected topics in data analytics. If we had a required management science course that covered simulation and optimization, I would like to follow the suggestion of Leong and Cheong (2008) and focus strictly on basic data analysis, modeling, spreadsheet engineering, and application development in the BAM class. Since the inception of the course, I have used two textbooks: Practical Management Science (Winston and Albright 2011) and VBA for Modelers (Albright 2009).…”
Section: Lab Based Coursementioning
confidence: 99%